68 Task Specificity in Fall Prevention. (20th December 2019) - Lord, Stephen
Abstract: Falls pose a major threat to the well-being and quality of life of older people. Falls can result in fractures and other injuries, disability and fear and are can trigger a decline in physical function and loss of autonomy. This presentation with synthesises recent published findings on fall risk and mobility assessments and fall prevention interventions and considers how this field of research may evolve in future, Fall risk topics include the utility of remote monitoring using wearable sensors and recent work investigating brain activation and gait adaptability. New approaches for exercise for fall fall prevention including dual task training, cognitive-motor training with exergames and reactive step training are discussed. The presentation will discuss how these new initiatives and technologies have potential for effective fall prevention and improved quality of life. It concludes by emphasising the need for a continued focus on translation of evidence into practice including robust effectiveness evaluations of so that resources can be appropriately targeted into the future.